2012
DOI: 10.1029/2012gl051912
|View full text |Cite
|
Sign up to set email alerts
|

Significant concentrations of nitryl chloride observed in rural continental Europe associated with the influence of sea salt chloride and anthropogenic emissions

Abstract: We present the first measurements of nitryl chloride (ClNO2) over continental Europe. Significant quantities of ClNO2, up to 800 pptv, were measured at a mountaintop field site in Hessen, southwest Germany. ClNO2 was detected during the majority of nights between the 15th August and 16th September 2011, its largest mixing ratios being associated with air masses influenced by sea salt and anthropogenic NOx emissions. ClNO2 persisted in measurable quantities until early afternoons on days with low photolysis fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
240
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(256 citation statements)
references
References 32 publications
15
240
1
Order By: Relevance
“…These results indicated ubiquitously observed ClNO 2 in the NCP, although high ClNO 2 mixing ratios have also been previously observed in both marine and continental environments in North America, Europe, and Asia Mielke et al, 2011;Thornton et al, 2010;Phillips et al, 2012;Tham et al, 2014). The average nitrate radical production rate p(NO 3 ) was 2.8 and 3.6 ppbv h −1 during P1 and P2, respectively, which are both higher than those during P3 and P4 (1.7-2.6; Table 1).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These results indicated ubiquitously observed ClNO 2 in the NCP, although high ClNO 2 mixing ratios have also been previously observed in both marine and continental environments in North America, Europe, and Asia Mielke et al, 2011;Thornton et al, 2010;Phillips et al, 2012;Tham et al, 2014). The average nitrate radical production rate p(NO 3 ) was 2.8 and 3.6 ppbv h −1 during P1 and P2, respectively, which are both higher than those during P3 and P4 (1.7-2.6; Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…Phillips et al (2012) also reported large variability in N 2 O 5 and ClNO 2 correlations and ClNO 2 /N 2 O 5 ratios in air masses from continental or marine origins due to the changes in particle Cl − . In this study, ClNO 2 was well and positively correlated with N 2 O 5 during all four nights (Fig.…”
Section: Relationship Between N 2 O 5 and Clnomentioning
confidence: 90%
See 2 more Smart Citations
“…ClNO 2 ) resulting from the heterogeneous reactions of N 2 O 5 with chloride containing particles (Osthoff et al, 2008;Thornton et al, 2010;Phillips et al, 2012;Ammann et al, 2013;Phillips et al, 2016).…”
mentioning
confidence: 99%